COMPARATIVE EFFICACY OF TWO HORMONAL TREATMENTS FOR OESTRUS INDUCTION IN ANOESTRUS CROSSBRED COWS - D. Abdul Salam; K. Murugavel; M.S. Raju (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted to assess the efficacy of two oestrus induction protocols on 30 postpartum anoestrus crossbred cows reared by rural farmers of Puducherry region. The cows were randomly divided into Treatment I (CIDR+PGF2α+GnRH; n=15) and Treatment group II (Ovsynch+ CIDR; n=15) with double fixed timed inseminations at 12 and 24 hours post-administration of last GnRH. Oestrus induction response was 100% in both the treatment groups with majority of the cows (80%) in both the treatment groups showed intermediate intensity of oestrus. The mean time to onset of oestrus from the time of removal of CIDR in Treatment I and Treatment II was 43.45 ± 9.21 and 45.81 ± 6.34 h respectively. There is no significant difference in the serum progesterone concentration at the time of AI between Treatment I (0.92±0.26 ng/mL) and Treatment II (0.92±0.18 ng/mL). Though the conception rate was higher in treatment II (40 %) compared to Treatment I (20 %), the difference is not statistically significant. From the present study, it was concluded that Ovsynch in combination with CIDR found to be effective in oestrus induction and conception following fixed timed AI in anoestrus cows under field conditions.